Atomic-scale study on segregation behavior at austenite grain boundaries in boron- and molybdenum-added steels. (July 2017) - Takahashi, J.; Ishikawa, K.; Kawakami, K.; Fujioka, M.; Kubota, N.
Abstract: The addition of small amount of boron (B) to steels has been found to significantly increase the hardenability of steels during cooling. This is further increased by the addition of molybdenum (Mo) and the combined addition of both. To clarify the mechanism of the Mo-B combined addition effect, quantitative analysis of segregating atoms at prior austenite grain boundaries in B- and Mo-added low-carbon (C) steels was performed using atom probe tomography. The dependences of Mo content and cooling rate on the amounts of B and Mo segregations were systematically investigated in the steels with austenizating temperature of 950 °C. The amount of B segregation at the prior austenite grain boundary was mostly independent of Mo content at a high cooling rate of 30 °C/s. In contrast, at a low cooling rate of 5 °C/s, the amount of B segregation increased in the B-added steel with Mo, and decreased without Mo, whereas the amount of Mo segregation increased with increasing Mo content and with lowering cooling rate. Such segregation behaviors of B and Mo were explained by the diffusion limited equilibrium segregation and precipitation of Fe23 (CB)6 at the austenite grain boundary. We discussed the influence of B and Mo segregations on hardenability from the relation between hardenability index and actual segregation amount in the steels. Graphical abstract: Image